2022
DOI: 10.1155/2022/9558511
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Virtual Clinics in Postoperative Total Knee Replacement Surgery Follow-Up during COVID-19 Pandemic

Abstract: Background. The purpose of this study was to evaluate the feasibility of the virtual clinic for outpatient follow-up care after TKR surgery. Methods. A total of 546 TKR surgeries were performed from January 2017 to December 2019. 30 patients were not able to go the hospital for routine follow-up. The data collections were taken for age, gender, year of surgery, functional score (Oxford Knee Score (OKS)), and active range of motion (ROM). The virtual clinic was conducted with the physician assistant and the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Studies by Pamuk[ 5 ] and Stahl et al [ 8 ] demonstrated the reliability of WhatsApp for teleconsultation and decision-making in orthopaedic trauma, respectively, with findings suggesting near-perfect agreement with traditional diagnostic methods. Further, Kapıcıoğlu et al [ 26 ] affirmed the safety and reliability of using WhatsApp for decision-making regarding paediatric supracondylar fractures, and Sumargono et al [ 27 ] reported high satisfaction rates with virtual clinics using WhatsApp for postoperative follow-up after total knee replacement surgery, emphasizing its potential continuity beyond the pandemic context.…”
Section: Evidences Of Whatsapp In Medical Care and Medical Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Pamuk[ 5 ] and Stahl et al [ 8 ] demonstrated the reliability of WhatsApp for teleconsultation and decision-making in orthopaedic trauma, respectively, with findings suggesting near-perfect agreement with traditional diagnostic methods. Further, Kapıcıoğlu et al [ 26 ] affirmed the safety and reliability of using WhatsApp for decision-making regarding paediatric supracondylar fractures, and Sumargono et al [ 27 ] reported high satisfaction rates with virtual clinics using WhatsApp for postoperative follow-up after total knee replacement surgery, emphasizing its potential continuity beyond the pandemic context.…”
Section: Evidences Of Whatsapp In Medical Care and Medical Teachingmentioning
confidence: 99%
“…The COVID-19 pandemic underscored the value of virtual fracture clinics as a cost-effective strategy. Sumargono et al [ 27 ] and Kauta et al [ 44 ] demonstrated how virtual supervision and co-management by orthopaedic teams through WhatsApp referral groups enabled non-specialist physicians to successfully treat a significant portion of traumatic fractures at community health clinics. This not only facilitated timely and efficient care but also minimized the need for in-person consultations, which was particularly advantageous during the pandemic[ 45 ].…”
Section: Non-clinical Applications Of Whatsapp In Healthcarementioning
confidence: 99%